PIRANTI KOMPUTASIONAL SYSTEMIC CODER SEBAGAI ALAT BANTU ANALISIS TEKS BERBASIS SYSTEMIC FUNCTIONAL GRAMMAR - Wiedarti, Pangesti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2005)
This article first presents the Systemic Functional Grammar(SFG), developed by Halliday (1985, 1994) and Halliday andMatthiessen (2003), one grammar that can be used in languageanalysis. Then it describes briefly the use of the Systemic Coder (SC),a computational tool developed by O'Donnell (1994) that is especiallybeneficial for linguists to employ in language analysis based on SFGwhen they have to deal with huge corpora and need quick resultsas it facilitates getting comprehensive data characteristics in arelatively short time. SC is applicable in Indonesia as its platform isthe commonly used MSWord and it can be utilized in analyzing anylanguage employing the Latin alphabet. There are other advantagesof SC application, which understandably requires, among others,one's mastery of SFG.Keywords: systemic functional grammar, systemic coder, languageanalysis